UUniversalisme Islam dan Kontribusinya dalam Konstruk Indonesia Baru - Umi Sumbulah (el Harakah: Jurnal Budaya Islam, 2000)
New Indonesia, until this era still become an issue. Various forums of seminars and dialogues are held in order to find meaning and format forward the figure of a new Indonesia. The concept of Islamic universalism and its contribution in the New Indonesia construct can depart from the thought of the concept of al dharnriyat al khamsab, which of course includes its all-encompassing human and humanitarian history of Indonesia, which in many ways is diversity, in accordance with the concept of rahmatan Iil al alamin. Each component of the nation is required to have a prerequisite in the form of independence and democratization which includes freedom, justice and equality. Prerequisites intended, demanding implementation not only by the community but also good will and political will from the ruling elite. The actualization of the values of Islamic universalism in order to lead to New Indonesia is not just a mere academic camouflage. Indonesia baru, hingga detik inipun masih menjadi bahan perbincangan yang cukup menarik. Berbagai forum seminar dan dialog diselenggarakan dalam rangka mencari makna dan format ke depan sosok Indonesia baru. Konsep universalisme Islam dan konstribusinya dalam konstruk Indonesia Baru dapat berangkat dari pemikiran tentang konsep al dharnriyat al khamsab, yang tentu saja pemanahannya mencakup seluruh manusia dan perjalanan sejarah kemanusiaan Indonesia, yang dalam banyak hal bersifat diversity, sesuai dengan konsep rahmatan Iil al alamin. Setiap komponen bangsa diharuskan memiliki prasyarat berupa independensi dan demokratisasi yang meliputi freedom, justice dan equality. Prasyarat dimaksud, menuntut implementasi tidak hanya oleh masyarakat tetapi juga good will and political will dari elite penguasa. Teraktualisasikannya nilai-nilai universalisme Islam dalam rangka menuju Indonesia Baru bukan hanya kamuflase akademik belaka.